ROBERTO SCHWARZ AND THE DEACTIVATION OF THE UNIVERSALITY OF BRAS CUBAS - Couto, Elvis Paulo [UNESP] (2020)
The purpose of this paper is to question the validity of one of Roberto Schwarz's arguments in A master on the periphery of capitalism: Machado de Assis. In this work, Schwartz directly opposes the possibility of investigating The posthumous memoirs of Bras Cubas from a universalist point of view, presenting, instead, a Marxist analysis centered on the process of formalization of the conduct of the Brazilian ruling class at the time of the Empire. Some notes from the main representatives of Machado's critical fortune are used to refute the thesis that only an historical-sociological interpretation can reveal the meaning of the first modern Brazilian novel.